2018
DOI: 10.3892/ol.2018.9727
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of CADM1 and CADM4 in triple negative breast cancer with primary systemic therapy

Abstract: Triple negative breast cancer (TNBC) is defined by a lack of ER, PgR, and HER2 expression, and to date there have been no significant advances in treatment by targeted therapies against those molecules. Therefore, primary systemic therapy (PST) followed by surgery is the standard therapy for patients with advanced TNBC. According to gene expression analysis, TNBC has a distinct profile when compared with non-TNBC, suggesting that a unique gene affects the treatment efficacy of PST. Cell adhesion molecule (CADM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In addition, overexpression of CADM4 was efficient in suppressing the tumorigenicity of cancer cells [8,9,11]. Similar to these results, a decrease in or loss of expression of CADM4 in tumor cells was associated with aggressive clinicopathological phenotypes and poor prognosis, suggesting the potential of CADM4 as a tumor suppressor [10,[12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 73%
“…In addition, overexpression of CADM4 was efficient in suppressing the tumorigenicity of cancer cells [8,9,11]. Similar to these results, a decrease in or loss of expression of CADM4 in tumor cells was associated with aggressive clinicopathological phenotypes and poor prognosis, suggesting the potential of CADM4 as a tumor suppressor [10,[12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 73%
“…The transcription factor GATA3 is overexpressed in lower grade breast tumors with a better prognosis, while its low levels are correlated with larger tumors [ 21 , 22 ]. Similarly, a lack of expression of the cell adhesion molecule CADM1 is associated with an advanced tumor stage, suggesting that inactivation of CADM1 promotes breast cancer development [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Motonobu et al found that CADM1 downregulation promoted advanced breast cancer progression and was strongly associated with tumor malignancy. 22 Deletion of CADM1 expression in bladder cancer was associated with adverse pathological factors, and overexpressing CADM1 in bladder cancer cell lines resulted in reduced cell proliferation and invasion rates. 23 Li et al found that CADM1 is a target of miR-486 in ovarian cancer cells, and this regulation could affect cell cycle progression and apoptosis.…”
Section: Discussionmentioning
confidence: 99%